Sosialisasi Dalam Mendorong Penggunaan Barang Ramah Lingkungan di SDN 12 Sesetan - Andistan, Ignacia Betrya; Laksmi P, Kadek Wulandari (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
Community service through real work lectures (KKN) is a form of student contribution in overcoming problems in the community. This service aims to increase the awareness of elementary school students on the importance of using environmentally friendly goods as a form of effort to preserve the environment where students do not understand the use of environmentally friendly goods. Socialization is carried out through an educational approach involving presentations, interactive discussions, and practical activities such as the introduction of alternative eco-friendly goods. The target of this activity is grade 6 students at SD Negeri 12 Sesetan. The results of the activity showed that students were able to understand the concept of using environmentally friendly goods and were able to apply them by bringing their own drinking bottles and using cloth shopping bags. This activity is able to have a positive impact on increasing students' understanding of the importance of maintaining an environment from an early age.     Keywords: eco-friendly goods; Socialization; Environmental Awareness; Elementary School Students; Plastic Waste Abstrak: Pengabdian kepada masyatarat melalui kuliah kerja nyata (KKN) merupakan salah satu bentuk kontribusi mahasiswa dalam mengatasi permasalahan yang ada di masayarakat. Pengabdian ini bertujuan untuk meningkatkan kesadaran siswa sekolah dasar terhadap pentingnya penggunaan barang ramah lingkungan sebagai bentuk upaya menjaga kelestarian lingkungan yang mana siswa belum paham penggunaan barang-barang yang ramah lingkungan. Sosialisasi dilakukan melalui pendekatan edukatif yang melibatkan presentasi, diskusi interaktif, dan kegiatan praktek seperti pengenalan alternatif barang ramah lingkungan. Sasaran dari kegiatan ini adalah siswa/i kelas 6 di SD Negeri 12 Sesetan. Hasil kegiatan menunjukkan bahwa siswa/i mampu memahami konsep penggunaan barang ramah lingkungan dan mampu menerapkannya dengan membawa botol minum sendiri dan menggunakan tas belanja kain. Kegiatan ini mampu memberi dampak positif terhadap peningkatan pemahaman siswa/i tentang pentingnya menjaga lingkugan sejak usia dini.Kata kunci: Barang Ramah Lingkungan; Sosialisasi; Sadar Lingkungan; Siswa SD; Sampah Plastik